Detection of Fasciola sp. in the Livers of Slaughtered Cattle at a Slaughterhouse in North Lombok Regency - Syamsuddin, Syamsuddin; Ningtyas, Novarina Sulsia Ista'in; Purwanti, Ni Luh Lasmi; Supriadi, Supriadi (Universitas Airlangga, 2024)
Background: Fasciola sp. has been identified as a highly pathogenic organism and has a significant health impact on both animals and humans. However, there is a lack of data and information on fasciolosis in North Lombok Regency. Purpose: This study aims to detect the presence of Fasciola sp. in livers of slaughtered cattle at the Tanjung Sub-district Slaughterhouse, North Lombok Regency. Methods: This study was conducted on the livers of slaughtered cattle, with a total of 30 samples collected between August and September 2023. Results: A total of 30 liver samples from slaughtered cattle at the Tanjung Sub-district Slaughterhouse, North Lombok Regency were examined for the presence of Fasciola sp. worms. The examination involved observing changes in color, size, consistency, and palpation of the organ. Following the incision of the liver and bile ducts and subsequent inspection of several areas with pathological-anatomical changes due to the infestation of Fasciola sp., an average length and width measurements of Fasciola sp. worms were found to be 26 mm and 6.4 mm, respectively. This indicated the worms belong to the Fasciola gigantica species. Conclusion: The results of this study indicated that Fasciola sp. worms were found in the livers of slaughtered cattle at the Tanjung Sub-district Slaughterhouse, North Lombok Regency. The worms were identified as belonging to the Fasciola gigantica species, characterized by an average length of 26 mm and width of 6.4 mm, having a narrow shoulder, a blunt posterior end, a flat leaf-like body shape, dorsoventrally flattened, a brownish-gray color, and an oral sucker at the anterior end.